Asasmen Perkembangan Kognitif Anak Usia 4-5 Tahun Melalui Pembelajaran di Kelas Taman Kanak Kanak - Putri Cantika Siregar; Rinby Dwi Andini; Tengku Nuraini Sukma Putri; Dinda Amelia; Chairin Nur Syahda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve the cognitive development of children aged 4–5 years through observation of learning activities in a kindergarten. This study uses a descriptive observation method with five children as subjects. Observations were conducted for two days to observe children's abilities in several cognitive aspects, including the ability to find solutions when facing difficulties, group small and large objects, mention numbers 1–10, and distinguish between various colors. Data were collected through field notes using assessment instruments compiled based on indicators of early childhood cognitive development. The results of the study showed that most children were in the Very Well Developed (BSB) category for all observed indicators, although there were some children who were in the Developing According to Expectations (BSH) category. These findings indicate that the learning strategies implemented by educators have been able to stimulate cognitive development optimally, and can be used as a reference in compiling further learning programs.